Scaling analysis of the electrohydrodynamic atomization (EHDA) process for pharmaceutical particle fabrication - Rezvanpour, Alireza. (2013)
Electrohydrodynamic Atomization (EHDA), also referred to as the electrospray process, has been recently developed to fabricate polymeric micro- or nano-particles as well as fibers for drug encapsulation. EHDA in the cone-jet mode can produce highly monodisperse aerosols. As a result of strong electric forces, liquid droplets can be created by the electrospray process and converted into solid particles. In this study EHDA was carried out in a glass chamber in which solid pharmaceutical particles were fabricated after evaporating the solvent from sprayed droplets. A high voltage nozzle with a concentric ring and a grounded collection plate were enclosed in an EHDA glass chamber. A modified design for the glass chamber was used in this study in which the particles are collected inside the chamber. The effects of different parameters on the particle collection efficiency were experimentally investigated. Important factors affecting the particle collection efficiency were the flow rate of the liquid solution used to create the particles, the nitrogen flow rate and the nozzle voltage. Systematic scaling analysis was conducted on the governing equations in the current EHDA system. The final results confirmed that the particle acceleration, gravitational and Saffman lift forces are not important in comparison to the electrical field and flow field forces for the EHDA apparatus and conditions used in this study. Furthermore, scaling analysis of the describing equations for the electrospray process permitted collapsing all the collection efficiency data onto a universal plot as a function of one dimensionless group that incorporates all the process parameters. This plot can be used to determine the effect on the collection efficiency of changing the liquid solution flow rate, nitrogen flow rate and nozzle voltage as well as geometrical parameters such as length and diameter of the chamber, and location of the collection plate.